PENERAPAN METODE BLENDED LEARNING DALAM PEMBELAJARAN PAI PADA ERA NEW NORMAL - Risky Aviv Nugroho (LPPM STAI DARUSSALAM LAMPUNG, 2021)
This study aims to determine the application of the Blended Learning Method in PAI learning in the new normal era. This study uses a qualitative approach with interviews, observations and documentation as data collection techniques. The results of this study are: blended learning method is to combine two or more learning methods. Its application to PAI learning at SD Rejowinangun 1 Yogyakarta goes through three stages, namely (1) planning: preparing lesson plans and materials; (2) implementation: online, offline, and face-to-face consultation with health protocols; (3) evaluation. The advantage of this method is that the material can be conveyed comprehensively and the drawback is that it can potentially be exposed to the covid-19 virus because there is face-to-face. The expected positive impact from the results of this research is as information to educational institutions that Blended Learning is an alternative that is very suitable to be applied in the Covid19 Pandemic Era.